PENENTUAN SEKTOR BASIS DAN NON BASIS DI KOTA AMBON - Louisa Manuhutu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2016)
Regional economic development is essentially a series of activities carried out by vernmen area, together withthe communities in managing and utilizing existing resources optimally to stimulate regional economic developmentin order to improve living standards for people in the area. Gross Regional Domestic Product (GDP) in Indonesiaessentially consists of nine sectors, namely (1) the agricultural sector; (2) mining and quarrying; (3) processingindustry; (4) electricity, gas and water; (5) building and construction; (6) trade, hotels and restaurants; (7)transport and communications; (8) the financial, leasing and business services; and (9) services. This study aims todetermine the basic sector and non base in Ambon City. Metodo data analysis used in this research is the analysis ofLQ (Location Quatient) to measure the concentration rather than something or industrial activity in a region bycomparing its role in the economy of the area with industrial activities same role in the national economy. Theresults of the analysis of LQ (determination of the basic sector and non-base) of the sectors of the economy showsthat are included in the basic sector is the sector of transport and communications, financial services, leasing andbusiness services, the services sector and the sector of electricity, gas and water supply. They include the sectorwhile the non bases are agriculture, mining and quarrying, manufacturing and construction sector.